Acculturation Architecture Traditional Makassar to Residential Development as the Humanistic - ., Imriyanti; Wunas, Shirly; Arifin, Mimi (International Journal of Engineering and Technology, 2019)
House, itâ€™s a part of architecture that is very important in human life. The house is used in interaction, activities and as a shelter. The houses in Giring-Giring hamlet in the Kalaseâ€™rena village, sub district of Bontonompo, district of Gowa are still Makassar tradisional houses, but following the occuparts needs and the increase of economic demand the houses form underge architectural acculturation. The acculturations impilicate occuparts needs, their activities and changing factors to be considered. This research method is descriptif qualitative, There is to explain the house development parts and functions. The houses atterns still maintain the â€œsiringâ€ (under parts) home room (middle part) an â€œpammakkangâ€ (attic) as its trditional architecture. In the living room the maintain there areas namely â€œpaddaserang ri dallekangâ€ (front part), paddaserang ri tangga (middle part) and â€œpaddaserang ri bokoâ€ (back part). The materials of the houses are consisting of both woods/bamboo (traditional ones) and brick/cement (modern ones) as a means both to empower and to reduce the cost of the housesÂ